Predictive value of ultrasound scoring in relation to clinical and histological parameters in xerostomia patients. (12th September 2018) - Jazzar, Ahoud; Manoharan, Andiappan; Brown, Jackie E.; Shirlaw, Penelope J.; Carpenter, Guy H.; Challacombe, Stephen J.; Proctor, Gordon B.
Abstract: Background: Salivary gland dysfunction is one of the main clinical features of Sjögren's syndrome (SS), manifested by xerostomia with subsequent complications and well‐established effects on the person's quality of life. Objectives: To determine firstly whether selected tests of salivary gland function and structure, unstimulated whole salivary flow rate (UWSFR), parotid flow rate (PFR), clinical oral dryness score (CODS) and ultrasound score (USS), can discriminate SS from non‐SS sicca patients and secondly whether these tests can differentiate between patients in different subgroups of SS. Method: Unstimulated whole salivary flow rate, PFR, CODS and USS were determined in 244 patients comprised of SS patients ( n  = 118), SS patients at higher risk of lymphoma ( n  = 30) or with lymphoma ( n  = 26), and non‐SS sicca disease controls ( n  = 70). Results: All assessments showed a significant difference between the overall SS group and the disease control group, attributed mainly to the lymphoma subgroups of SS ( p  < 0.0001 for all parameters). There was a significant correlation (Spearman r  = 0.7, p value <0.0001) and 87.3% agreement between USS and the histology focus scores of 119 patients. Conclusion: The results suggest that salivary gland tests including USS can aid in differentiating between SS and non‐SS dry mouth, especially the subgroups of SS with lymphoma or at higher risk of developing lymphoma.